PERANCANGAN SISTEM INFORMASI PENGELOLAAN DATA TENAGA HARIAN LEPAS PADA DPU PENGAIRAN KABUPATEN BANYUWANGI - Imroatin Nur Arifah; Abd. Ghofur; Husnul Chotimah (CV. Denasya Smart Publisher, 2025)
The management of Non-Permanent Daily Workers (THL) at the Public Works and Water Resources Department of Banyuwangi Regency is still carried out manually, making it inefficient and error-prone. This study aims to develop a web-based information system to improve the process of recording, searching, and reporting THL data. The research applied both library and field studies through interviews, observation, and documentation. The system was developed using the prototyping method within the Software Development Life Cycle (SDLC). The resulting system provides features for faster data input, storage, and report generation, ensuring information is more accurate and accessible. Its implementation is expected to reduce data errors, streamline administrative tasks, and support better decision-making in managing THL.